Half-wave-crystal channeling of relativistic heavy ions at super-FRS GSI/FAIR; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 486 - Bogdanov O. V. Oleg Viktorovich; Pivovarov Yu. L. Yury Leonidovich; Tukhfatullin T. A. Timur Ahatovich; Geissel H. Hans; Kuzminchuk-Feuerstein N. A. Natalia Aleksandrovna; Purushothaman S. Sivaji; Scheidenberger Ch. Christoph (2021, 2021)
Title screen